DO COMMUNISTIC MEMORIALS WANT TO LIVE FOREVER? MEMORIAL’S PARKS IN COUNTRIES OF CENTRAL AND EASTERN EUROPE - Czarnecka, Dominika (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
With the fall of the communist regime, the largest wave of iconoclasm since the French Revolution has begun in the countries of Central and Eastern Europe. Thousands of statues of communist leaders and heroes were spectacularly destroyed; however, not all of them shared the same fate. Some monuments were directed to specially organized monuments parks and museums. The article examines reasons behind the birth of new institutions after 1989, their functions and methods of displaying communist monuments, and thus, constructing narratives about the past. Problems of memory and the policy of memory implemented thanks to this kind of theme parks, were also discussed.